IMPLEMENTASI SISTEM MANAJEMEN MUTU ISO 9001:2008 PADA PT METABISULPHITE NUSANTARA - Marbun, Syafriningsih Laila; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the implementation, the supporting and the inhibiting factor and the benefit in implementing the Quality Management System ISO 9001:2008 on PT Metabisulphite Nusantara. The result of this research describes that the requirements of Quality Management System ISO 9001:2008 have been fulfilled by PT Metabisulphite Nusantara. However, in the 7th clausal, the realization of product to be exact in 7.3 clausal, the development and design has not been carried out by PT Metabisulphite Nusantara. The supporting factors i.e.: fund, involvement and cooperation of all parties, compliance and consistency of the employees, the fulfillment of a facilities, the modern technology and information system. The inhibiting factor is there are some employees who have been found that they are lack of comprehension of ISO 9001:2008. The employees need to adapt and to try hard to comprehend on what will be targeted. The benefits in the implementation are: the achievement of companyâs vision and mission is more systematic, efficiency and effective, profit has increased, trust and satisfaction of the end-users product has made the enhancement of the number of customers, the work is more focus and directed, the documentation system is getting better, a well supervised quality system, and the enhancement of the image of PT Metabisulphite Nusantara.Keywords: Implementation, Quality Management System, ISO 9001:2008.